The Effect of the On Call Work System on Work Fatigue in Tanah Grogot Hospital Employees - Suyatno; Evi Mulyaningsih (Global Writing Academica Researching and Publishing, 2023)
Ideal working hours are 8 hours a day or 40 hours a week but the On Call work system exceeds this requirement. One of the jobs that do the work of the On Call system is service work in hospitals. Employees on call tend to arrive late due to various factors including fatigue. This study aims to determine the effect of the On Call Work System on Work Fatigue in Tanah Grogot Hospital Employees. This study used a Quasi-Experimental Design with a one-way simple randomized design. The results of the study showed that there was an effect of the On Call Work System on the Level of Work Fatigue experienced by Tanah Grogot Hospital employees. Employees with On Call 1 Work Systems have a higher Work Fatigue Level than employees with On Call 2 and Non On Call Work Systems. Employees with the On Call 2 work system have a higher Fatigue Level than employees with the Non On Call Work System.